Structural difficulties of building a consensus in the rok legislative system - Kim, Dong hyun (KDI School, 2011)
Consensus building has often been used as an effective means to resolve dispute among interest groups in a highly democratic societies. As Republic of Korea has shifted from its dictatorship to a fully recognized democracy since the 90s, demands for achieving successive consensus building have started to gain recognition. Yet, many attempts failed in reaching a consensus in Republic of Korea when a “highly political involvement” took place. This study strives to get into the epicenter of such failures-The National Assembly in Republic of Korea, “the arena of politics”, where it is infamous for an excessive Win-Lose power struggle. Of course, sometimes it may be the nature of politics to strategically neglect the consensus building with the rivaling parties. However, National Assembly in Republic of Korea seems excessive in attempting to obstruct the opponent parties that “consensus building often does not reflect the needs of their people. Such excessive tendency of political rivalry combined with the reality of non-existence in having an effective consensus building mechanism may risk neglecting the needs of their people. Therefore an effective method of consensus building is demanded in ROK’s legislature system. Through the ROK media law passing case, this study attempts to articulate the current structural flaws which obstruct gaining an effective consensus building mechanism in the National Assembly. By identifying what and why it is so difficult in having an effective consensus in the “political arena” of ROK, this paper would contribute to the future discovery for obtaining better modeling and alternatives
Thesis(Master) --KDI School:Master of Public Policy,2011